2001
DOI: 10.2307/1423515
|View full text |Cite
|
Sign up to set email alerts
|

Memory of Action Events: The Role of Objects in Memory of Self- and Other-Performed Tasks

Abstract: Encoding action phrases by enactment produces better recall than hearing or reading the action phrase. This study examined whether enactment enhances memory relative to observing another perform the same action. Theories of the enactment effect suggest that the complexity of the action, here manipulated by varying the number of objects involved in an action, may determine whether enactment enhances memory relative to observation. The results revealed a consistent subject-performed task advantage across all obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 0 publications
1
19
3
Order By: Relevance
“…The analysis revealed main effects of encoding [F(1,35) There are several aspects of the results to consider. First, the main effect of encoding condition demonstrates the advantage of enactment encoding over observing during encoding (e.g., Engelkamp & Zimmer, 1997;Hornstein & Mulligan, 2001). Second, the SPT condition replicates Engelkamp et al's (1994) results in finding that reenactment at test enhances recognition accuracy for items enacted at study.…”
Section: Resultssupporting
confidence: 64%
“…The analysis revealed main effects of encoding [F(1,35) There are several aspects of the results to consider. First, the main effect of encoding condition demonstrates the advantage of enactment encoding over observing during encoding (e.g., Engelkamp & Zimmer, 1997;Hornstein & Mulligan, 2001). Second, the SPT condition replicates Engelkamp et al's (1994) results in finding that reenactment at test enhances recognition accuracy for items enacted at study.…”
Section: Resultssupporting
confidence: 64%
“…Much of the literature (e.g., Hornstein & Mulligan, 2001;Zimmer & Engelkamp, 1985) explains the facilitation in terms of allocentric and egocentric information. For example, Zimmer and Engelkamp distinguished between kinematic (spatial location in visual space) and kinesthetic (muscle feedback) information components, and reported a partial dissociation in their representation in memory.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, better recall performance should be found in self-performed action than observed action, but their argument was not supported by Cohen (1981Cohen ( , 1983, who found no difference in later recall between self-performed and observed enactment, or Saltz and Donnenwerth-Nolan (1981), who found no difference between self-performed and imagined enactment. However, in subsequent studies, the recall advantage of self-performed over observed action was obtained by Engelkamp and Zimmer (1997) and Hornstein and Mulligan (2001). They argued that the inconsistency between the empirical findings was caused by the study design; the effects of self-23 performed tasks often occur in within-subject designs, rather than between-subject designs used by Cohen (1981Cohen ( , 1983) and Saltz and Donnenwerth-Nolan (1981).…”
mentioning
confidence: 99%